Karakteristik Merokok Dan Tekanan Darah Pada Pria Usia 30-65 Tahun: Cross SectionalStudy - Heriviyatno J Siagian; La Ode Alifariki; Tukatman Tukatman (Jurnal Kesehatan Komunitas, 2021)
The smoking habit is still a health behavior problem that affects various organs in the body, especially the cardiovascular system. The chemical content in one cigarette has an effect on heart health and changes blood pressure. This study aims to determine the relationship between smoking characteristics in men aged 30-65 years in Kolaka Regency. This research was conducted in several Kelurahan in Kolaka Regency using a cross sectional study design involving 112 respondents who were selected by purposive sampling with certain criteria. The collected data were then processed and analyzed using the chi square test at the alpha significance limit of 0.05. The results showed that all the variabels that were part of the smoking characteristics were related to the respondent's blood pressure. The variabel number of cigarettes, duration of smoking, types of smoking and method of smoking cigarettes has a p value of 0.000. It is concluded that smoking can increase blood pressure in men aged 30-65 years.